Extra Virgin Olive Oil Improves Oxidative Stress, Functional Capacity, and Health-Related Psychological Status in Patients With Fibromyalgia: A Preliminary Study. (January 2017) - Rus, Alma; Molina, Francisco; Ramos, Manuel Miguel; Martínez-Ramírez, María Josefa; del Moral, María Luisa
Objectives: Fibromyalgia (FM) is a chronic disease that imposes physical, psychological, and social limitations. We have reported that oxidative stress may play a role in the pathophysiology of FM. Olive oil has been shown to be effective treatment against the oxidative stress associated with several diseases. The aim of this study was to investigate the effect of olive oil on oxidative stress and health-related parameters in FM. Methods: This preliminary study was performed on blood samples of 23 women diagnosed with FM who consumed 50 ml of organic olive oil daily for 3 weeks. Subjects were randomized into two groups: one ingested extra virgin olive oil (EVOO) and the other refined olive oil (ROO), which have different antioxidant content. The patients' oxidative (lipid, protein, and DNA oxidation) and antioxidative (antioxidant enzyme activities and compounds) profiles were examined before and after the treatment period. Functional capacity and physical and mental health status were assessed using the Fibromyalgia Impact Questionnaire (FIQ) and the Physical Component (PCS-12) and Mental Component Summaries (MCS-12) of the Short Form-12 Health Survey, respectively. Results: Significant differences were found in pre–post change between the EVOO and ROO groups for protein carbonyls, lipid peroxidation, and FIQ and MCS-12 scores. Differences between groups approached statistical significance for oxidative DNA damage and levels of the antioxidant compound zinc. Conclusions: EVOO may protect women with FM against oxidative stress in addition to improving functional capacity and health-related psychological status. Findings suggest that olive oil may be a valuable therapeutic support in FM.